The Relationship Between Nutritional Status and Diet Patterns and Anemia in Adolescent Girls at MA Jamilurrahman Bantul Yogyakarta - Tarisa, Tarisa Wilsa Athala; Khofiyah, Nidatul (Jurnal Kebidanan Midwiferia, 2025)
Anemia is the impact of nutritional problems in adolescent girls. Nutritional anemia is caused by a lack of nutrients that play a role in the formation of hemoglobin, which can be due to lack of consumption or abortion disorders. The impact of anemia that can occur in adolescent girls is a decrease in immunity which causes adolescent girls to be susceptible to disease. The Bantul Regency Health Office conducted a Hemoglobin examination in 2022 on 700 adolescent girls in Bantul, the results of the health office found 29% or 203 adolescent girls suffering from anemia. With the value stating that there are two variables that have a relationship with nutritional status with the incidence of anemia, namely (p-value 0.001) and the relationship between diet and the incidence of anemia, namely (p-value 0.009). Health workers are expected to be able to provide services in schools, especially related to anemia management by preventing anemia through counseling related to adolescent nutrition and anemia and conducting anemia screening by conducting hemoglobin examinations. Based on the results of research on the relationship between nutritional status and eating patterns and anemia in adolescent girls at MA Jamilurrahman Bantul Yogyakarta, it was found that there was a relationship between nutritional status and the incidence of anemia.